2022
DOI: 10.47577/tssj.v38i1.7963
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the real estate market on the economic development of Constanța County

Abstract: At the local level, the promotion of sustainable economic development by creating a favorable business development climate and new employment opportunities is necessary to increase the well-being and development of communities. The economic and social mechanism of the real estate market guides economic agents’ activity, being influenced by its relationship with other sectors of the economy, such as construction, trade, tourism, the financial banking system and, last but not least, the management of local publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The two cities are the capitals of the two countries; they were chosen as examples of large capitals of post-communist countries. They were also the case studies from a 2012 study (Ianoş et al, 2012), which revealed some similarities with respect to their urban dynamics, especially with respect to land use conflicts due to the socialist interventions in the city center and post-communist developments in the fringes, aimed mostly for profit (Aivaz, 2021;Stan, 2022b). The study, published close to the midpoint of the period we analyzed, emphasizes a stronger implementation of environmental policies in Romania after the accession to the European Union.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two cities are the capitals of the two countries; they were chosen as examples of large capitals of post-communist countries. They were also the case studies from a 2012 study (Ianoş et al, 2012), which revealed some similarities with respect to their urban dynamics, especially with respect to land use conflicts due to the socialist interventions in the city center and post-communist developments in the fringes, aimed mostly for profit (Aivaz, 2021;Stan, 2022b). The study, published close to the midpoint of the period we analyzed, emphasizes a stronger implementation of environmental policies in Romania after the accession to the European Union.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there are studies looking at the differences in land use and its changes between Eastern and Western Europe, such as more changes due to less stable political regimes in Eastern Europe (Kupková et al, 2013;Rusu et al, 2020), and prominence of changes like urbanization (Kupková et al, 2013;Petrişor et al, 2020) and cropland abandonment (Baumann et al, 2011;. The core principle allowing for comparisons across Eastern European countries is the fact that countries within the area share a communist background followed by a post-communist transition, often related to the European Union accession (Legutko-Kobus et al, 2023; Nowak et al, 2022), and, as a result, more centralized planning systems (Stan, 2021(Stan, , 2022bSlave et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The role of public administration in sustainable urban development, and how age can influence perceptions of socio-economic issues, has been extensively analyzed (Stan, 2014(Stan, , 2022a(Stan, , 2022b(Stan, , 2022c. Similarly, Jung and Ha-Brookshire (2017) have highlighted the influence of individual attributes like age on sustainability perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of public administration in sustainable urban development has been analyzed extensively by Stan (2014;2022a;2022b;2022c). These studies provide valuable insights into how gender might influence the perception of socio-economic issues like green spaces management, the impact of the real estate market on economic development, and passenger transport's potential for sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%